2012
DOI: 10.1523/jneurosci.0136-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Neurophysiology of Language in Adults: Relationship to Regional Cortical Thinning and White Matter Microstructure

Abstract: Although reading skill remains relatively stable with advancing age in humans, neurophysiological measures suggest potential reductions in efficiency of lexical information processing. It is unclear whether these age-related changes are secondary to decreases in regional cortical thickness and/or microstructure of fiber tracts essential to language. Magnetoencephalography, volumetric MRI, and diffusion tensor imaging were performed in 10 young (18–33 years) and 10 middle-aged (42–64 years) human individuals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 61 publications
(74 reference statements)
6
12
0
Order By: Relevance
“…The higher the immediate memory, the lower the central atrophy. To our knowledge in this, the largest study utilizing 3T MRI and NeuroQuant, our results are in agreement with the literature [ 56 , 58 62 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher the immediate memory, the lower the central atrophy. To our knowledge in this, the largest study utilizing 3T MRI and NeuroQuant, our results are in agreement with the literature [ 56 , 58 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our current study, NeuroQuant measured hippocampal atrophy in individuals versus age-matched controls as normative percentile, so the effect of age upon hippocampal atrophy was not assessed. However, we did find age to be significantly correlated with small vessel ischemia (p < 0.0001) [ 55 ]; Reduced FA [diffusion imaging technique thought to reflect fiber density, axonal diameter, and white matter demyelination] in frontal lobes (p = 0.0134) [ 56 ] and bilateral atrophy (p = 0.0067) [ 57 ]. In terms of FA status we found a number of interesting correlations.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found in older adults more than in younger adults during grammatically complex sentence reading [ 23 ] and speech perception [ 19 ]. Similarly, previous studies have also found age-related under-recruitment in lexical semantic processing [ 17 ], word recognition [ 47 ], and semantic coding [ 48 ]. Under-recruitment may reflect not enough resources [ 2 ] in older adults engaged in high demand tasks.…”
Section: Discussionsupporting
confidence: 61%
“…In a functional MRI study (fMRI), Stebbins et al (2002) found less activation in left prefrontal cortex in older adults relative to younger adults while they carried out a single-word semantic judgment task. Using magnetoencephalography (MEG), Kemmotsu et al (2012) compared young to middle-aged adults (mean age of 50 years-old) during single-word semantic judgment task, and reported that middle-aged adults recruited the inferior prefrontal region to a lesser extent than young adults. Thus, even when the impact of working memory load and syntactic demands was reduced by presenting single-words, patterns of prefrontal hypoactivation were still observed in older adults during semantic judgment, even though behavioral performance was equivalent across groups.…”
Section: Discussionmentioning
confidence: 99%